Reliability in Automotive and Mechanical Engineering Determination of Component and System Reliability - Bertsche, Bernd (VDI-Buch, 2008)
In the present contemporary climate of global competition in every branch of engineering and manufacture it has been shown from extensive customer surveys that above every other attribute, reliability stands as the most desired feature in a finished product. To survive this relentless fight for survival any organisation, which neglect the plea of attaining to excellence in reliability, will do so at a serious cost Reliability in Automotive and Mechanical Engineering draws together a wide spectrum of diverse and relevant applications and analyses on reliability engineering. This is distilled into this attractive and well documented volume and practising engineers are challenged with the formidable task of simultaneously improving reliability and reducing the costs and down-time due to maintenance. The volume brings together eleven chapters to highlight the importance of the interrelated reliability and maintenance disciplines. They represent the development trends and progress resulting in making this book essential basic material for all research academics, planners maintenance executives, who have the responsibility to implement the findings and maintenance audits into a cohesive reliability policy. Although, the book is centred on automotive engineering nevertheless, the examples and overall treatise can be applied to a wide range of professional practices. The book will be a valuable source of information for those concerned with improved manufacturing performance and the formidable task of optimising reliability.